OPTIMIZING GUIDANCE AND COUNSELING THROUGH NIAS LOCAL WISDOM TO ENHANCE STUDENTS’ SCIENTIFIC ATTITUDES AND PROBLEM-SOLVING SKILLS - Darmawan Harefa (Universitas Nias Raya, 2026)
This study aims to examine the effectiveness of optimizing guidance and counseling (GC) services through the integration of Nias local wisdom in enhancing students’ scientific attitudes and problem-solving skills at SMA Negeri 1 Telukdalam. This research employed a quasi-experimental design with a non-equivalent control group. The sample consisted of tenth-grade students divided into an experimental group and a control group. The experimental group received guidance and counseling services integrated with Nias local wisdom, while the control group received conventional services. Data were collected using a scientific attitude scale and a problem-solving skills test, administered through pre-test and post-test procedures. The data were analyzed using descriptive and inferential statistics, including paired and independent samples t-tests. The results showed a significant improvement in both scientific attitudes and problem-solving skills among students in the experimental group compared to the control group (p < 0.05). The findings indicate that the integration of Nias local wisdom into guidance and counseling services creates a more meaningful and culturally relevant learning environment. This approach enhances students’ engagement, critical thinking, and ability to solve problems effectively. Therefore, culturally responsive guidance and counseling can be considered an effective strategy to support students’ holistic development.